HEPCIDIN PADA ANEMIA OF CHRONIC DISEASE - Agustriadi, Ommy; Suega, Ketut (journal of internal medicine, 2012)
Anemia of chronic disease (ACD) induce dysregulation of iron homeostasis. A hallmark of anemia of chronic disease is the development of disturbances of iron homeostasis, with increased uptake and retention of iron within cells of the reticuloendothelial system (RES), that leads to a diversion of iron from the circulation into storage sites of RES, and decreased intestinal iron absorption, subsequent limitation of the availability of iron for erythroid progenitor cells, and iron-restricted erythropoiesis. A new small peptide called hepcidin was found. It is strongly suggest that hepcidin play role on the pathogenesis of ACD. Hepcidin expression is induced by inflammation/infection (by lipopolysaccharide and interleukin-6) and iron overload condition, it is strongly suggest that hepcidin induced dysregulation of iron homeostasis by inhibit iron efflux from macrophage dan RES (causing iron retention in turn) and decrease intestinal iron absorption. In the aggregate, the increase of hepcidin production suppress erythropoiesis by iron starvation strongly suggest that hepcidin is the key mediator of ACD. If hepcidin follows the pattern of other peptide hormones or cytokines, its actions will be mediated by cell surface receptors. Elucidation of the receptor and its transduction pathways should lead to the development of hepcidin antagonists, some of which could be useful in treatment of ACD, along with it's underlying disease.
Keywords: hepcidin, anemia of chronic disease, iron metabolism